Pendampingan Literasi Membaca Santri Melalui Cerpen Berbahasa Arab Berbasis Literacy Cloud - Wulandari Wulandari; Mia Fatimatul Munsi; Anis Silmi Qauli (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2025)
COMMUNITY SERVICE ON ENHANCING STUDENTS’S READING LITERACY THROUGH ARABIC SHORT STORISE USING LITERACY CLOUD.This Service Learning activity is focused on Pesantren Hidayatul Muhajirin in Cirebon. There are two main focuses in this service: First, on how the culture of reading Arabic short stories (cerpen) is practiced at Pesantren Hidayatul Muhajirin Cirebon. Second, on the implications of implementing the reading of Arabic short stories through the Literacy Cloud in shaping the reading literacy culture at Pesantren Hidayatul Muhajirin Cirebon. This Service Learning activity is crucial to assess the extent to which the implementation of reading Arabic short stories through the Literacy Cloud device influences the habituation of reading culture among the students (santri) at Pesantren Hidayatul Muhajirin. Through this habituation, it is expected that Arabic short stories can be learned and understood more easily. The method employed in this community service is the Participatory Action Research (PAR) approach. The subjects or participants in this service include the Pesantren caretakers, several male and female Islamic scholars (ustadz/ustadzah), as well as male and female students (santriwan and santriwati). Data collection for this service involves observation, interviews, and documentation. The results of the service show that the reading literacy at Pesantren Hidayatul Muhajirin has not been well-formed. The guidance provided in reading Arabic short stories through the Literacy Cloud has an impact on the formation of reading literacy among the students, shifting the perception of Arabic short stories from initially being perceived as difficult to becoming easy and enjoyable.